Comparative Effects of Problem-Based Learning, Creative Problem Solving, and Problem Posing on Junior High School Students' Mathematical Reasoning - Nurhanurawati Nurhanurawati; Nurain Suryadinata; Siti Mutmainah (FKIP Universitas Lampung, 2026)
Junior high school students in Indonesia consistently face systemic challenges in their mathematical reasoning skills, leading to consistently poor performance on international tests like PISA. This enduring educational disparity underscores an immediate need for pedagogical reforms that transcend rote memorization and promote approaches that foster cognitive adaptability. Our study was driven by the need to evaluate and compare the efficacy of three prominent student-centered frameworks: Problem-Based Learning (PBL), Creative Problem Solving (CPS), and Problem Posing, in enhancing students' reasoning outcomes. Our study utilized a quasi-experimental design featuring a post-test-only control group. The sample consisted of 93 seventh-grade students from Bandar Lampung. The data underwent statistical testing because the CPS group exhibited a non-normal distribution, as determined by preliminary normality testing (Sig. = 0.000). Therefore, the non-parametric Kruskal-Wallis Test was employed to ensure analytical integrity. The findings revealed a statistically significant disparity in reasoning achievement across the three experimental groups (Asymp.Sig. = 0.006). Detailed pairwise comparisons using the Bonferroni correction demonstrated that while PBL and CPS yielded comparable results (Adj.Sig. = 1.000), likely due to their shared reliance on structured problem-solving foundations, the Problem Posing model emerged as the most potent intervention. It significantly outperformed both PBL (Adj. Sig. = 0.007) and CPS (Adj. Sig. = 0.035). This superiority stems from the unique cognitive demands of problem-solving, which necessitate that students engage in thorough, divergent thinking and careful structural analysis of mathematical concepts. This model enhances metacognitive skills essential for advanced reasoning by transforming students' roles from problem solvers to creators. This study recommends problem posing as a core approach for educators aiming to improve students' mathematical reasoning. Keywords: mathematical reasoning, problem posing, problem-based learning, creative problem solving.